2014
DOI: 10.1016/j.electacta.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A single-ion gel polymer electrolyte system for improving cycle performance of LiMn2O4 battery at elevated temperatures

Abstract: a b s t r a c tThe LiMn 2 O 4 based lithium batteries using commercially available electrolytes suffer from poor cycling performance at elevated temperatures (above 55• C). This is mainly caused by the Mn dissolution generated from HF thermally decomposed from the LiPF 6 salt at elevated temperatures. In this paper, a single-ion gel polymer electrolyte (polymeric lithium tartaric acid borate @ poly(vinylidene fluoride-cohexafluoropropylene) was explored for improving the cycling performance of the LiMn 2 O 4 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 35 publications
0
38
0
4
Order By: Relevance
“…[63] For example, the lithium tartaric acid borate (PLTB)-based single lithium-ion conducting GPEs were demonstrated to improve the cyclic performances of LiMn 2 O 4 /Li cell and obviously alleviate the generation of lithium dendrites on Li anodes, compared with LiPF 6 -based electrolyte at elevated temperature of 55 °C. [68] Similarly, the ionic conductivity is also critical for the practical application of single lithium-ion conducting GPEs, which are governed by the ionic mobility in polymer hosts. To this end, a promising approach to increase the Li + ion mobility in gel polymer is to enhance the segmental motion of the polymer backbone by lowering their T g or introducing polymer backbones with low T g than that of the room temperature.…”
Section: Single Lithium-ion Conducting Gpesmentioning
confidence: 99%
“…[63] For example, the lithium tartaric acid borate (PLTB)-based single lithium-ion conducting GPEs were demonstrated to improve the cyclic performances of LiMn 2 O 4 /Li cell and obviously alleviate the generation of lithium dendrites on Li anodes, compared with LiPF 6 -based electrolyte at elevated temperature of 55 °C. [68] Similarly, the ionic conductivity is also critical for the practical application of single lithium-ion conducting GPEs, which are governed by the ionic mobility in polymer hosts. To this end, a promising approach to increase the Li + ion mobility in gel polymer is to enhance the segmental motion of the polymer backbone by lowering their T g or introducing polymer backbones with low T g than that of the room temperature.…”
Section: Single Lithium-ion Conducting Gpesmentioning
confidence: 99%
“…Furthermore, during the charging and discharging, it takes a few cycles to facilitate Li + ion pathways between the electrolyte and electrode as well [53]. Certainly, there has been reported that it needs the activation process to activate electrodes [54][55][56]. So it may well be that these coefficient reasons described above give rise to the activation process.…”
Section: Activation Processmentioning
confidence: 99%
“…As shown in Fig. 2c, the PP separator, Naon membrane and the Nf-PP-Li separator all have high thermal decomposition temperatures over 300 C. 19 So the Nf-PP-Li separator exhibited better thermal stability. According to the DSC curves shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The ion conductivity of the PP substrate at room temperature is 4.98 Â 10 À4 S cm À1 . Since a high lithium ion transference number has long been pursued, 19 preparation or introduction of the -SO 3 Li groups has proved to be an effective method and is expected to alleviate ion concentration gradients, decreasing internal resistance and alleviating interface polarization within lithium ion batteries. the bulk resistance of the Naon based material is much higher, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation